2010
DOI: 10.1038/nsmb.1876
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and age-specific DNA replication patterns at the CTG/CAG-expanded human myotonic dystrophy type 1 locus

Abstract: Myotonic dystrophy, caused by DM1 CTG/CAG repeat expansions, shows varying instability levels between tissues and across ages within patients. We determined DNA replication profiles at the DM1 locus in patient fibroblasts and tissues from DM1 transgenic mice of various ages showing different instability. In patient cells, the repeat is flanked by two replication origins demarcated by CTCF sites, with replication diminished at the expansion. In mice, the expansion replicated from only the downstream origin (CAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 66 publications
3
75
1
Order By: Relevance
“…Mapping of replication origins by nascent strand analysis in a mice model of myotonic dystrophy, showed that the expanded triplet repeat was replicated in the CAG orientation [63]. When the level of Msh2 or Msh3 was reduced in these same mice, expansions were reduced too.…”
Section: Similarities and Differences Between Mammalian And Yeast Modelsmentioning
confidence: 99%
“…Mapping of replication origins by nascent strand analysis in a mice model of myotonic dystrophy, showed that the expanded triplet repeat was replicated in the CAG orientation [63]. When the level of Msh2 or Msh3 was reduced in these same mice, expansions were reduced too.…”
Section: Similarities and Differences Between Mammalian And Yeast Modelsmentioning
confidence: 99%
“…Transgenic and knock-in mouse models that recapitulate the expansion of the DMPK TNRs showed that the integration site and the amount of flanking human genomic sequence affect TNR instability (19,28,35,77,79). These findings suggest that cis-acting elements may play a crucial role in determining TNR stability during normal differentiation or pathological states.…”
mentioning
confidence: 97%
“…Relevant to studies of the relationship between the DNA replication and (CAG) n · (CTG) n stability is a comparison of origin activity at the DMPK locus in human control and DM1 fetal fibroblasts and transgenic mice (19). In this work, two origins were identified, upstream and downstream of the DMPK (CAG) n · (CTG) n repeats, in control and DM1 human fibroblasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no effect of Dnmt1 deficit was seen on somatic instability (Dion et al, 2008). Another study, which investigated somatic instability of the DM1 CTG repeat in relation to replication and CTCF binding, has led to the suggestion that CpG methylation may regulate, in a tissue-specific manner, the role of CTCF in DNA replication and thereby CTG repeat instability (Cleary et al, 2010). Yet another connection between DNA methylation, CTCF and TNR expansion has been identified in studies of SCA7 transgenic mice, which revealed further destabilization of unstable expanded CAG repeats by CpG methylation of CTCF binding sites (Libby et al, 2008).…”
Section: Modulation Of Tnr Instabilitymentioning
confidence: 99%